Evaluation of Vehicle Parking Queueing in a National Park: Case Study of the Laurance S. Rockefeller Preserve in Grand Teton National Park. Issue 1 (2017) - Fuentes, Antonio; Heaslip, Kevin; D'Antonio, Ashley; Khalilikhah, Majid; Soltani-Sobh, Ali
In national parks, there is a tension between providing areas for vehicles and accommodating other visitor activities in the park. This tension often means there is more demand for vehicle parking than the supply can accommodate. This study examined one of Grand Teton National Park's (GRTE) visitor attractions with visitor parking provided, the Laurance S. Rockefeller Preserve (LSR) in Jackson, Wyoming. With approximately 54 designated parking spots available, a study to determine the queueing theory measures of performance was conducted under observed and higher-value parameters to evaluate the system. It was determined that under the observed average arrival rate of 25 vehicles per hour (vph) and 35 vph with an average service rate (time a vehicle was parked) of 1 h and 20 min, the system resulted in good performance with a facility utilization value of 61% and 84%, respectively. However, under the higher-value parameters, the results were poorer, with facility utilization values greater than 88%. This study provides a reference for the evaluation of performance measures and can be applicable to future changes in the LSR at GRTE, other national parks parking, or in general parking areas where queueing may be anticipated.